ETNOMATEMATIKA PADA MOTIF KAIN (HIOU) BULANG SIMALUNGUN - Munthe, Lasmarintan Natalia; Ayu Silaen; Kasih Simanjutak; Gracea Damanik; Friska Ledina Situngkir (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to explore the mathematical concepts contained within the motifs of the Hiou Bulang, the traditional head covering worn by Simalungun women, as an effort to find effective learning solutions. The approach utilized is ethnography, focusing on intensive cultural exploration to uncover the implementation of formal mathematical concepts within traditional knowledge. The findings reveal that the motifs of the Hiou Bulang significantly contain ethnomathematics concepts in the field of geometry. The concepts identified include transformational geometry such as 180° rotation (in the Sidomu hail and Bituha boyok motifs) and translation (in the Rayungan sonduk motif), as well as plane geometry concepts like fold symmetry (Jumbu tuou), two parallel lines (Suhi ampang and Goli-goli), and the triangle shape (Pahu-pahu patuddal marbuah tabu). These findings substantiate that local culture can serve as an attractive and effective concrete learning medium to enhance students' comprehension of mathematical concepts.